Perencanaan Zonasi Kawasan Pesisir Berbasis Aktivitas Ekonomi - Miftahunnisa Rusli; Mukti Ali; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
This study aims to identify economic activities of the community and formulate directions for coastal zoning based on economic activities. The analysis technique used in this research is analysis of distribution patterns to determine the zoning direction of economic activity. The results of the study showed that Bulu Cindea Village had quite diverse economic activities. However, in the implementation of economic activities there are still some who are not yet in accordance with the criteria standards including limited supporting facilities, community industrial businesses are still underdeveloped and distribution patterns that have not been directed in accordance with applicable rules and not accompanied by zoning stipulations. The zoning directives which are formed consist of four zones namely capture fisheries activity zone consisting of fishing zones, industrial zones and marketing zones, zones of aquaculture and salt cultivation activities consisting of supplier zones, industrial zones and marketing zones and agricultural activity zones consisting of zones suppliers, distributor zones and marketing zones.